Designing Productive Parks - From Romanticizing Agriculture towards Green Infrastructure and Productive Public Space: The Ruhr Metropolis as a Laboratory for Productive Parks. - Timpe, Axel (Lit, 2020)
The way landscape architects react to challenges in new public park designs is examined in the PhD research "Designing Productive Parks - history and current practice of bio-based production in European parks." (Timpe 2017) The research strategy used is a comparative analysis of case studies drawn from practice (plan analysis) and research by design (experimental design studies). Out of 34 possible case studies identified in Europe, 18 have undergone a deeper analysis. The research process has proven that the Ruhr Metropolis is a hotspot in the development of productive parks; five cases have been analyzed there. As these five cover the whole period considered in the study (since 1990), they are an ideal example of the evolution that the conception of productive parks has undergone. The case studies, which extend back over the last 25 years, show that the concept of the productive park as a laboratory for new land use is one that is gradually emerging in the Ruhr Metropolis. While early examples are dominated by a romantic orientation towards historic land use systems, more recent examples demonstrate the intention to integrate production with other functions of green and blue infrastructure and to define productive spaces as public spaces.
Keywords: Freiraumplanung; Landschaftspark; Flächennutzung; Flächenbewirtschaftung; Biomasse; Nahrungsmittelproduktion; Biodiversität; Altindustrie; Industriefläche; Nutzungsänderung; Produktiver Park